Paths towards transformative agency - Creating repertoires for socio-educational change - Ola Erstad; Raquel Miño-Puigcercós; Pablo Rivera-Vargas (Acta Psychologica)
A key issue in understanding the transformation and future orientations of education and learning is how we engage students in processes of learning and development and how this is embedded within the communities they belong to. We need to move beyond aspects of socio-cognitive and emotional approaches to learning and development, towards what has been called transformative agency. The role of educational psychology in understanding these developments is especially important since it raises fundamental aspects of the human condition in times of dramatic change and the experiences of young people. Our aim in this article is to explore key aspects of the term transformative agency as repertoires for social change across institutions of formal education and everyday practices of students. We initially explored and identified a set of emerging initiatives from around the world and selected four relevant cases for closer analysis. Our research questions focus on: how transformative agency is defined and emerge in four projects from Northern Europe, Southern Africa, Brazil and Australia; which are the purposes and practices in engaging students to enhance transformative agency in different sociocultural contexts; and which are the socio-educational implications in the four analysed initiatives to foster transformative agency. These emerging initiatives all have in common that they show how students are involved in learning processes in ways of opening up schools to the wider communities. To conclude, we show both the possibilities, and constraints and challenges encountered by such bottom-up initiatives.